2019
DOI: 10.1039/c9tc01831j
|View full text |Cite
|
Sign up to set email alerts
|

Combining GeO2 passivation strategies aiming at dielectric layers with superior properties on germanium substrates

Abstract: Hf and N incorporation in GeO2 suppresses its volatilization and further oxidation of the Ge substrate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Consequently, hindered the growth of unstable GeO x compounds and reduced volatile GeO desorption while maintaining the integrity of GeO 2 . 55,56 Therefore, based on the Ge 3d spectra observation it can be suggested that 10 minutes sample exhibits the superior configuration of stoichiometric contents with a minority composition of GeO x traps that might help in improving the device performance of the high-k interface.…”
Section: Xps Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, hindered the growth of unstable GeO x compounds and reduced volatile GeO desorption while maintaining the integrity of GeO 2 . 55,56 Therefore, based on the Ge 3d spectra observation it can be suggested that 10 minutes sample exhibits the superior configuration of stoichiometric contents with a minority composition of GeO x traps that might help in improving the device performance of the high-k interface.…”
Section: Xps Analysismentioning
confidence: 99%
“…It is assumed that substantial incorporation of N+ atom increases Ge 3 N 4 density at this oxidation/nitridation durations which obstructed the O vacancy diffusion paths and also retarded the disproportionate transportation of O atoms into the Ge substrate. Consequently, hindered the growth of unstable GeO x compounds and reduced volatile GeO desorption while maintaining the integrity of GeO 2 55,56 . Therefore, based on the Ge 3d spectra observation it can be suggested that 10 minutes sample exhibits the superior configuration of stoichiometric contents with a minority composition of GeO x traps that might help in improving the device performance of the high‐ k interface.…”
Section: Physical and Electrical Characterizationmentioning
confidence: 99%